Meningkatkan Kemampuan Membaca Siswa melalui Tekhnik Permainan Bahasa Melengkapi Cerita - Nur Fadilah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2018)
One of factors in the decline of student ability is due to the lack of teacher creativity in the teaching and learning process, especially in Bahasa Indonesia subjects that contain text material so it tends to be boring if it only delivered through lectures. The method (field research) with a descriptive qualitative approach was used in this study, because the researcher went directly to the research location. Researchers use interviews, observations, etc. in data collection. This research shows that when the teacher uses the language game technique to complete the story of the students, the teacher is finally able to improve the ability of the second grade students of Madrasah Ibtidaiyah Nurul Islam Uranggantung, even by using the language game technique to complete the story, students are able to win the poetry reading contest at the district level.